PENGARUH COMPUTER ANXIETY DAN COMPUTER ATTITUDE TERHADAP KEAHLIAN PENGGUNA KOMPUTER - Wahyudi, Ridwan; Widianto, Tri (JURNAL AKUNTANSI DAN INVESTASI, 2019)
This study empirically examines the influence of Computer Anxiety and Computer Attitude on Computer User Skills with Locus of Control (LoC) as a moderating variable in students of the Accounting Study Program STIE AUB Surakarta. The research method used is the Moderated Regression Analysis (MRA) Test.             Data collection techniques using a questionnaire, the sample in this study were students of the Accounting Study Program STIE AUB Surakarta who had taken accounting computer courses totaling 153 students. Linearity test results showed the value of R2 0.225 with 153 observations, the calculated c2 value = 153 x 0.235 = 35.96 while the c2 table value was 51.26. C2 value calculated <c2 table so that it can be concluded that the correct model is a linear model.             In the first hypothesis test the regression coefficient of computer anxiety (β1) is 0.281829 meaningful if the computer anxiety variable has a positive relationship on the variable of computer user expertise with the locus of control variable as moderation. In the second hypothesis test, the coefficient of computer attitude (β2) is 1.237174 which means that if the computer attitude variable has a negative relationship on the variable of computer user expertise with the locus of control variable as moderation. The use of LoC as a moderating variable for the Computer Anxiety dimension in the expertise of computer users Accounting Surakarta STUB AUB Study Program is effective. Independent samples test shows that there is no significant difference between computer anxiety of male and female computer users.